Study Confirms Biosimilarity of HD203 and Etanercept in Patients with RA - Rizzo, Toni (MD Conference Express, 2014)
The new agent HD203 is a biosimilar of etanercept, a recombinant fusion protein that blocks tumor necrosis factor activity. The amino acid sequence of HD203 is identical to that of etanercept and is produced by the same method. The objective of the Trial to Evaluate Equivalence in Efficacy and Safety of HD203 and Enbrel in RA Patients [HERA; NCT01270997] was to evaluate the equivalence in efficacy of HD203 and etanercept in combination with methotrexate in patients with rheumatoid arthritis (RA).